Quo Vadis Brand Love? Role of Cognition-Affection-Behavior Model for Local Coffee Shops in Indonesia - Dea Farahdiba (Universitas Muria Kudus, 2023)
This study aims to identify the structural relationship between image, experience, love, trust, and brand loyalty for branded local coffee shops using the cognitive-affective-behavior (C-AB) model. One hundred thirty-five respondents participated in this study, and data analysis was performed using the SmartPLS statistical tool with the PLS-SEM method. It was found that brand image and experience had a significantly positive relationship with brand love and trust. Brand love and brand trust also have a significant positive relationship with brand loyalty, according to the assessment of Indonesian people on their favorite local coffee shop brands. This study contributes to the literature that the C-A-B model can explain the factors that form brand loyalty in the local coffee shop industry. In practice, brand love and brand trust owned by local communities form brand loyalty relationships in local products. This study also shows the mediating effect of brand love and brand trust for branded local coffee shops. Brand Love indirectly mediates the relationship between Brand Image and Brand Loyalty, but Brand Trust does not directly mediate the relationship between Brand Experience and Brand Loyalty. This study's main limitation is using the brand love mark only for brand love. The dimension of the brand love mark as Brand Respect can be included in future research.